A low-power prototype of contactless field power controlled BLAC and BLDC motors. Issue 2 (13th September 2020) - Soni, Umesh Kumar; Tripathi, Ramesh Kumar
Abstract: In this paper, a new design configuration has been proposed in which a prototype of resonant inductive power transfer-based contactless power transfer to wound rotor has been developed which provides field power to brushless alternating current (BLAC) or brushless direct current (BLDC) motors without the use of permanent magnets in the rotor. Further, wound field in the rotor of DC motor can be powered without carbon brushes. The proposed design facilitates motor performance improvement by adding an extra dimension of field flux control, while the armature circuit is conventionally fed from position detection and commutation schemes. It contains a primary multilayer concentrated coil fed with high-frequency resonating AC supply or switched mode supply. A single layer helical secondary coil coaxially fixed on the shaft receives high frequency wireless AC power transmitted from primary coil. Fast rectifier inside the hollow shaft and DC filter provides the transferred DC power to field terminals in the rotor. It has been verified that rotor power can be varied linearly with linear variation in input DC power with the highest efficiency at the resonant frequency. Available power to the rotor remains invariable with rotational speed and angle, which is a necessary requirement for rotor field. DC voltage on the rotor terminals can be effectively controlled during standstill as well as during rotation at any speed.